The Swedish liming operation : a study about liming officers opinions about some aspects regarding ecology, economy and organization - Karlsson, Rebecka (SLU/Dept. of Aquatic Sciences and Assessment, 2013)
This is a study about the Swedish liming operation and the Swedish liming officer’s opinions of some aspects regarding ecology, economy and organization. The study objectives was motivated due to the recent changes in manuals for the assessment of limed waters and the suggested changes in decision making and decreased budget for liming. Moreover the anthropogenic acidification effects on the ecology are in many ways complex. Furthermore it was made in order to gain knowledge about the liming officer’s opinions in order to improve the ability to meet their needs regarding the assessment tools and also to investigate if other things can be improved concerning the liming operation. The study is also a step to increase the use of different stakeholder’s knowledge, opinions and experience in relation to the natural science about acidification and liming. The study is based on answers from an inquiry performed 2010 and on semi structural interviews conducted in 2012-2013. The result shows that the opinions about liming doses were changed between the inquiry and the interviews. Several liming officers see a possibility of further reductions of liming doses, if done systematically and based on adequate knowledge. The majority of the liming officers perceived the task of performing the new acidification assessment in 2010 as difficult, and the use of the acidification assessment as time consuming and uncertain. Alkalinity and color measurement before liming were considered useful by the liming officers. Fish data were considered reliable, but uncertainties with the parameter were also mentioned. Diatoms were further mentioned as reliable and several liming officers had increased the sampling. Regarding organizational aspects, the study shows that the administrative tasks take a lot of time. It further seems like the municipalities and the county administrative boards not have an active dialog about the relimed waters. The liming officers further perceive risks with the proposed changes of decision making and the reduced liming budget. The study concludes, among other things, that there might be a need for more sampling and data in order to perform the current acidification assessment. The liming officers should be offered more education and the acidification assessment should be made more user friendly. This study further acknowledges that more can be done to make the acidification assessment more available for other stakeholders as well as the public. An educative and interesting figure of the MAGIC model and the MAGIC library available at homepages and handbooks might increase this possibility.